PENGARUH PENGELOLAAN KEARSIPAN TERHADAP EFISIENSI KERJA KARYAWAN PADA PT. BPR PRISMA DANA MANADO - KAJUAL, ELENSYA; Areros, William A.; Asaloei, Sandra Ingrid (JURNAL ADMINISTRASI BISNIS, 2017)
This research is motivated by the problems found in Bank Prekreditan Rakyat (BPR) office of Prisma Dana Manado, which is in the management of archive that is not very productive using work time so that the work quickly accumulate and the limited of human resources. The purpose of this study is to find out how much influence of archival management to the work efficiency of employees at PT. BPR Prisma Dana Manado. And the constraints faced are the maintenance of records that there are still records stacked in the cabinet so that the archive becomes easily damaged and also difficult to recover when needed at all times. This can certainly hamper office work. Therefore, there is a need for good and organized archive management so that it is easier for employees to reinvent the archive quickly. Arrangement arrangement is one of the aspects that must be applied at the office to support the achievement of the goal of increasing productivity and efficiency of office work. In this research, the method used is descriptive quantitative research method by spreading questionnaire 50 respondents who become sample in this research. The data were collected by questionnaires that have been tested for their validity and reliability. And our data analysis is descriptive and inferential statistic, consisting of simple correlation coefficient and regression done by using program SPSS for windows version 24.0. The results showed that there is a significant influence between archival management on work efficiency. From these results are done and followed by analyzing the data obtained, then there is a significant influence between the influence of archival management on employee work efficiency at PT.BPR Prisma Dana Manado and this means the work hypothesis or alternative hypothesis accepted. this means there is a positive influence between the management of archives to the work efficiency of employees with a level of influence of 21.3%. for it suggested more increase again the existence of filing system and work efficiency. Keywords: Archives management, work efficiency.